Verified chronic severe giant cell myocarditis: an inevitable choice for heart transplantation - O. V. Blagova; Yu. A. Lutokhina; D. H. Ainetdinova; V. P. Sedov; A. N. Volovchenko; D. A. Parfenov; N. P. Mozheiko (Вестник трансплантологии и искусственных органов)
Myocarditis has polymorphic clinical manifestations and is one of the main causes of heart transplantation. We present a clinical case of a 43-year-old female patient who was admitted to the clinic with biventricular heart  failure (NYHA class 3–4). She periodically noted exacerbations of bronchitis against the background of prolonged smoking. Twenty-one months prior to hospitalization, she first noted a shortness of breath without an obvious connection with the infection. Her ejection fraction (EF) decreased to 34%, pleural and pericardial effusion was revealed. Coronary angiography found no abnormalities. However, MRI showed subendocardial contrasting of the  left ventricular (LV) apex. The diagnosis was myocarditis. Within six months, the patient received therapy with 30 mg/day prednisolone and cardiotropic therapy. Her shortness of breath intensified, and the lower extremities swelled. Examination in the clinic showed a sharp decrease in QRS voltage, QS complexes in the V1–V6 leads, dilation of all heart chambers, thrombus in the LV apical aneurysm, 16% EF, 3.9 cm VTI, 454 mmHg dp/dt, and a sharp increase in anticardiac antibody titers (up to 1:320). Endomyocardial biopsy was not performed due to the patient’s rapidly deteriorating condition, the need for cardiotonics, and signs of multiple organ failure. She was transferred to Shumakov National Medical Research Center of Transplantology and Artificial Organs, where extracorporeal membrane oxygenation was performed; orthotopic heart transplant was successfully performed. The patient’s condition was stable for the next year. Investigation of the explanted heart revealed a picture of giant cell myocarditis. Issues of diagnosis, possibility of a long-term chronic course, as well as methods of treatment of this variant of myocarditis, including the key role of heart transplantation, are discussed.